Salvage transoral laser microsurgery for early local recurrence of glottic squamous cell cancer - Zhimou Cai; Huijun Yue; Lin Chen; Yang Xv; Yun Li; Bingjie Tang; Yu Lin; Wenbin Lei (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background For recurrent laryngeal cancer, the feasibility of salvage transoral laser microsurgery (TLM) remains controversial. This study compared the efficacy of TLM and open partial laryngectomy (OPL) for treatment of early local recurrence of glottic squamous cell cancer (GSCC) and confirm the effectiveness of salvage TLM as a treatment option. Methods This retrospective study involved 55 patients with early local recurrent GSCC treated with TLM, and the oncologic outcomes, functional outcomes, hospitalization time and complications were compared with a group of 40 recurrent GSCC patients matched for clinical variables of TLM group, treated by OPL by the same team of surgeons. Results The 5-year overall survival and disease-specific survival rates were 65.8% and 91.5%, respectively, for 55 patients with rTis–rT2 stage treated by TLM and 77.1% and 94.7%, respectively, for 40 patients with rTis–rT2 stage treated by OPL (OPL group). In the TLM and OPL groups, the local control rates after 5 years were 77.5% and 79.3%, respectively, and the laryngeal preservation rates were 94.4% and 83.6%, respectively (p > 0.05). Compared with the OPL group, the complication rate (1.82%) and hospitalization duration (5.42 ± 2.26 days) were significantly lower in the TLM group (p < 0.05). Compared with the OPL group, postsurgical health-related quality of life and quality of voice were significantly better in the TLM group (p < 0.001). Conclusion Salvage TLM can be used as an effective treatment option for suitable patients after a full, comprehensive, and careful assessment of the characteristics of early locally recurrent glottic carcinoma. Graphical Abstract